High-performance blue perovskite light-emitting diodes based on the "far-field plasmonic effect" of gold nanoparticles. Issue 19 (17th April 2020) - Xu, Tianfei; Li, Wei; Wu, Xiaoyan; Ahmadi, Mahshid; Xu, Long; Chen, Ping
Abstract : Far-field plasmonic effect of Au nanoparticles was explored for high performance blue-light perovskite electroluminescent devices, achieving maximum luminance and external quantum efficiency as high as 1110 cd m −2 and 1.64%, respectively. Abstract : Metal halide perovskites have become the next-generation electroluminescent materials due to their excellent optoelectronic properties. In the last several years, there has been tremendous progress in the performance of red and green-light perovskite electroluminescent devices (PeLEDs) with external quantum efficiencies (EQEs) exceeding 14% and 21%, respectively. In contrast, blue PeLEDs are still in their infancy, due to their EQEs of below 1%. Therefore, the development of blue PeLEDs is sorely needed since blue light plays a vital role in achieving full-color and white-light emission. In order to improve the efficiency of blue PeLEDs, herein we introduce gold nanoparticles (Au NPs) into a poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) hole transport layer (HTL) to achieve a high performance blue PeLED with an emission wavelength of ∼475 nm. By introducing Au NPs, the optical properties of poly(ethylene oxide) (PEO):PEA2 (CsPbBr x Cl3− x ) n −1 PbBr4 perovskite films have been significantly improved leading to 3.8 times enhancement in fluorescence intensity. Based on this improvement, blue PeLEDs record a maximum luminance and EQE of ∼1110 cd m −2 and 1.64%, respectively, presenting one of the best performances among the blue PeLEDs reported so far. Finally, the PeLED performance improvement is attributed to the far-field surface plasmonic effect of Au NPs. This effect has originated from the interference between the original chromophore emission and the mirror-reflected emission of mirror-type substrates. This study not only reveals the function of Au NPs in the development of blue PeLEDs, but also offers new insights into the fundamental physics underlying the effect of surface plasmon resonance of Au NPs on perovskite light emitting devices.